Disordered-guiding photonic chip enabled high-dimensional light field detection - Zhijuan Gu; Weilun Zhang; Yu Yu; Xinliang Zhang (Nature Communications)
Abstract Full characterization of light intensity, polarization, and spectrum is essential for applications in sensing, communication and imaging. However, existing schemes rely on discrete, bulky components to capture polarization and spectrum separately, and suffer from detecting only a few values in each dimension. Here, we implement a compact disordered-guiding photonic chip with a neural network for single-shot high-dimensional light field detection. The disordered region introduces complex interference and scattering among polarized components, while the guiding region efficiently collects the outputs to on-chip photodetectors. This design encodes high-dimensional input into multi-channel intensities with high sensitivity, subsequently decoded by the neural network. Experimentally, the accurate detection of broad spectrum with mixed full-Stokes polarization states is realized with a polarization error of 1.2° and spectral resolution as high as 400 pm. Furthermore, the device demonstrates high-dimensional imaging with superior recognition performance over single-dimensional methods. This innovation offers a compact and high-resolution solution for high-dimensional detection.